New insights into the role of melatonin in photosynthesis. (5th June 2022) - Yang, Sijia; Zhao, Yuqing; Qin, Xiaolong; Ding, Chunbang; Chen, Yanger; Tang, Zizhong; Huang, Yan; Reiter, Russel J; Yuan, Shu; Yuan, Ming
Abstract : Review of the role of melatonin in photosynthesis, highlighting its involvement in protection of the photosynthetic apparatus, maintenance of photosynthesis, control of stomatal movement, and regulation of the photosynthetic carbon cycle. Abstract: There are numerous studies on enhancing plant resistance to stress using melatonin, but few studies about its effect on photosynthesis. Herein, we summarized the role of melatonin in photosynthesis. Melatonin regulates chlorophyll synthesis and degradation through the transcription of related genes and hormone signals. It protects photosynthetic proteins and maintains the photosynthetic process through improving the transcription of photosystem genes, activating the antioxidant system, and promoting the xanthophyll cycle. Melatonin potentially regulates plant stomatal movement through CAND2/PMTR1. Finally, it controls the photosynthetic carbon cycle by regulating the metabolism of sugar, the gluconeogenesis pathway, and the degradation and transport of transient starch.